Budaya Membaca Siswa Berprestasi (Analisis Modal Budaya Pierre Bourdieu pada Siswa SMA di Kota Blitar) - Melia Marisa Salsabila; Suyono Suyono (Jurnal Ragam Pengabdian, 2026)
This study examines the reading culture of high-achieving students at senior high schools in Blitar City through Pierre Bourdieu's Cultural Capital theory. Using a qualitative descriptive approach, data were collected through in-depth interviews, non-participant observation, and documentation involving high-achieving students, teachers, and school librarians. The findings reveal that reading culture has been deeply internalized as a personal need rather than merely an academic obligation. The analysis demonstrates the interaction of three forms of cultural capital: objectified capital, represented by physical facilities such as classroom reading corners, school libraries, and access to books; embodied capital, reflected in habitual reading practices developed since early childhood through family socialization and continuous literacy experiences; and institutionalized capital, manifested in academic achievements, competition certificates, and recognition as literacy ambassadors. The sustainability of students' reading culture is strengthened by intrinsic motivation, effective self-regulation, supportive family environments, and the implementation of the School Literacy Movement (GLS). However, digital media distraction remains a significant challenge that affects students' reading consistency and concentration. This study concludes that reading culture is the result of accumulated cultural capital supported by family, school, and individual factors, and it significantly contributes to academic achievement, critical thinking skills, lifelong learning habits, and the development of a sustainable literacy culture in schools.